2011
DOI: 10.1002/cncr.26014
|View full text |Cite
|
Sign up to set email alerts
|

Population‐level comparative effectiveness of laparoscopic versus open radical nephrectomy for patients with kidney cancer

Abstract: BACKGROUND:Because there is limited population-based evidence supporting the comparative effectiveness of laparoscopic radical nephrectomy (LRN) after its widespread adoption, we compared trends in hospital-based outcomes among patients with kidney cancer treated with LRN or open radical nephrectomy (ORN). METHODS: Using linked SEER-Medicare data, the authors identified patients with kidney cancer who were treated with LRN or ORN from 2000 through 2005. The authors measured 4 primary outcomes: intensive care u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…It presents virtually a nationwide, unbiased overview of all types of tumor nephrectomies undertaken in Germany and provides the most comprehensive and contemporary analysis of the use of nephrectomy for renal cancer treatment. Furthermore, we used all available comorbidity diagnoses (up to 100 ICD-10 codes) whereas previous studies used 3 [30], 6 [15], 15 [8], or up to 20 [7] diagnoses only to derive Charlson comorbidity index and complications.…”
Section: Discussionmentioning
confidence: 99%
“…It presents virtually a nationwide, unbiased overview of all types of tumor nephrectomies undertaken in Germany and provides the most comprehensive and contemporary analysis of the use of nephrectomy for renal cancer treatment. Furthermore, we used all available comorbidity diagnoses (up to 100 ICD-10 codes) whereas previous studies used 3 [30], 6 [15], 15 [8], or up to 20 [7] diagnoses only to derive Charlson comorbidity index and complications.…”
Section: Discussionmentioning
confidence: 99%
“…Predominantly, several important disease characteristics, such as those defined by the RENAL (radius, exophytic/endophytic properties, nearness of tumor to the collecting system or sinus in millimeters, anterior/posterior, location relative to polar lines) nephrometry score as initially proposed by the Fox Chase Cancer Center, are not available within the SEER Medicare database. That being said, large observational population‐based cohorts are often limited by the lack of detailed tumor characteristics, but remain widely used . Second, information on hospital and surgeon identification was not available for all identified patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in an observational study, the proportion of hospitals carrying out at least one laparoscopic nephrectomy per year increased from 4% to 26% from 1989 to 2003 . Given the increasing popularity of nephrectomies carried out by the laparoscopic approach, contemporary studies have reported that laparoscopic nephrectomy affords equal postoperative and functional outcomes, and equivalent cancer control outcomes relative to open nephrectomy …”
Section: Introductionmentioning
confidence: 99%
“…Although it is technically demanding, laparoscopy provides RCC patients improved quality of life during recovery period with decreased analgetic requirements, fewer complications, and more rapid convalescence [24, 25]. However, there are some reports about higher in-hospital mortality and more common failure to rescue after laparoscopy probably due to poor experience of surgeons and hospitals [24, 25]. Despite all the advantages, laparoscopic surgery can have several local and systemic consequences related to the induction of pneumoperitoneum used to facilitate the visual field.…”
Section: Discussionmentioning
confidence: 99%